Effects of garlic powder supplementation on metabolic syndrome components, insulin resistance, fatty liver index, and appetite in subjects with metabolic syndrome: A randomized clinical trial. (11th May 2021) - Sangouni, Abbas Ali; Alizadeh, Mohammad; Jamalzehi, Atena; Parastouei, Karim
Abstract : The prevalence of metabolic syndrome (MetS) is increasing. It is closely linked to nonalcoholic fatty liver disease. Garlic consumption as a strategy for the management of MetS has been suggested. We investigated the effect of garlic supplementation on MetS components, insulin resistance, fatty liver index (FLI), and appetite in subjects with MetS. Ninety subjects were assigned to receive 1, 600 mg/d garlic powder or placebo for 3 months. The primary outcomes included MetS components. The secondary outcomes included insulin resistance, FLI, and appetite. Garlic supplementation compared with the placebo led to a significant increase in high density lipoprotein‐cholesterol (4.5 vs. −1.8, p  < .001) and a significant reduction in waist circumference (−1.3 vs. 0.0, p  = .001), diastolic blood pressure (−6.7 vs. 0.0, p  < .001), systolic blood pressure (−7.7 vs. 0.5, p  < .001), triglyceride (−40.0 vs. 0.1, p  < .001), γ‐glutamyl transferase (−3.2 vs. 0.6, p  = .01), FLI (−5.5 vs. 0.1, p  < .001), insulin (−2.9 vs. −1.1, p  < .001), homeostatic model of assessment for insulin resistance (−0.5 vs. −0.3, p  < .001) and appetite (hunger: −11.7 vs. 1.7, p  < .001; fullness: 10.0 vs. 0.3, p  = .001; desire to eat: −6.7 vs. 2.1, p  < .001; and ability to eat: −11.5 vs. −1.0, p  < .001). Garlic improves MetS components, insulin resistance, FLI, and appetite.